Understanding Character Dialogue in Modern English Literature: A Qualitative Study on Students’ Cognitive Processes in Literary Learning - Yasin, Mohammad Ilham; Fikri, Moh. Hilman; Sudrajad, Wahyu; Dewi, Maharani (Journal of Development Research, 2025)
The present study investigates cognitive processes of students while understanding character dialogue in modern English literature through a qualitative approach. Highlighting inferential thinking and perspective-taking, the research aims to explore how learning individuals interpret and react to advanced literary dialogue. The findings of the study identify that learner apply inferential strategies to understand implied meaning, affective undertones, and relational dynamics in character dialogue. Furthermore, perspective-taking played a central role, as students were more able to empathize and interpret more deeply when they adopted multiple character perspectives. The study identifies challenges students face, such as the inability to maintain inferences and coping with novel points of view, particularly in cross-cultural contexts. Pedagogic implications indicate that the teaching of literature should explicitly promote inferential thinking, perspective-taking, and cultural awareness leading to a more empathetic, integrated reading of literature. The present study makes a contribution towards the increasing pool of literature documenting cognitive investment in literary learning that reveals how literary teaching can assist students' critical thinking and emotional intelligence through exploring character dialogue.